Functional similarities between pigeon 'milk' and mammalian milk: induction of immune gene expression and modification of the microbiota. - Meagan J Gillespie (Public Library of Science (PLoS), 2012)
Pigeon 'milk' and mammalian milk have functional similarities in terms of nutritional benefit and delivery of immunoglobulins to the young. Mammalian milk has been clearly shown to aid in the development of the immune system and microbiota of the young, but similar effects have not yet been attributed to pigeon 'milk'. Therefore, using a chicken model, we investigated the effect of pigeon 'milk' on immune gene expression in the Gut Associated Lymphoid Tissue (GALT) and on the composition of the caecal microbiota. Chickens fed pigeon 'milk' had a faster rate of growth and a better feed conversion ratio than control chickens. There was significantly enhanced expression of immune-related gene pathways and interferon-stimulated genes in the GALT of pigeon 'milk'-fed chickens. These pathways include the innate immune response, regulation of cytokine production and regulation of B cell activation and proliferation. The caecal microbiota of pigeon 'milk'-fed chickens was significantly more diverse than control chickens, and appears to be affected by prebiotics in pigeon 'milk', as well as being directly seeded by bacteria present in pigeon 'milk'. Our results demonstrate that pigeon 'milk' has further modes of action which make it functionally similar to mammalian milk. We hypothesise that pigeon 'lactation' and mammalian lactation evolved independently but resulted in similarly functional products.